Profile of an occupation - Packaging materials technologist - Schambeck, Arne [Verfasser] (My University, 2020)
"As e-commerce continues to flourish, more and more types of packaging are needed for a countless assortment of products ranging from chocolates to fridges. In 2018, the German folding box industry alone reported a production volume of 870,971 tonnes. But who is responsible for manufacturing all these different packaging materials, for ensuring that each product has the right packaging to protect it and for doing all of this in a way which conserves resources?" (author's abstract; BIBB-Doku)
Keywords: S 6.2 Fertigungsberufe; Verpackungsindustrie; Papier- und Verpackungsberuf; Packmitteltechnologe; Tätigkeitsmerkmal